IJAR 2019
DOI: 10.21474/ijar01/8763
|View full text |Cite
|
Sign up to set email alerts
|

A Random Projection Approach to Secure Medical Images.

Abstract: All our day"s work in this world of science is done with useful data. These useful data or information is extracted from raw facts. From the information, knowledge is gained. This knowledge is used by the customers for beneficial outcome. Here comes the concept of data mining. An important query arises as how to preserve these data. This concept is called as Privacy Preserving with Data Mining (PPDM). Many PPDM techniques are available to protect the data. The PPDM technique is useful in fields like medicine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With this technique, data can be more protective. e privacy level can be improved [25]. Binjubeir et al provided an intensive review of existing PPDM approaches and classified various methods that are used for data modification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With this technique, data can be more protective. e privacy level can be improved [25]. Binjubeir et al provided an intensive review of existing PPDM approaches and classified various methods that are used for data modification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They contrasted their algorithm with the perturbation strategy and demonstrated that their algorithm provided 100% data usefulness. Mary [14] asserts that the random projection strategy has a higher level of privacy than the other approaches. The photos can be very well maintained by employing RP.…”
Section: Introductionmentioning
confidence: 99%